Transglutaminase 2 Depletion Attenuates α-Synuclein Mediated Toxicity in Mice. (10th August 2020) - Zhang, Jie; Grosso Jasutkar, Hilary; Yan, Run; Woo, Jong-Min; Lee, Kang-Woo; Im, Joo-Young; Junn, Eunsung; Iismaa, Siiri E.; Mouradian, M. Maral
Highlights: TG2 deletion in α-synuclein (α-Syn) transgenic mice reduces brain α-Syn aggregates. Neuronal processes are better preserved in TG2 KO /α-Syn Tg mice than in α-Syn Tg mice. Neuroinflammatory response is also dampened in TG2 KO /α-Syn Tg mice. Motor performance of TG2 KO /α-Syn Tg mice is better preserved. Pharmacological inhibition of TG2 may be protective in α-synucleinopathies. Abstract: α-Synuclein (α-Syn) is a key pathogenic protein in α-synucleinopathies including Parkinson disease (PD) and Dementia with Lewy Bodies. The aggregation of α-Syn is believed to be deleterious and a critical step leading to neuronal dysfunction and death. One of the factors that may contribute to the initial steps of this aggregation is crosslinking through transglutaminase 2 (TG2). We previously demonstrated that overexpression of TG2 exacerbates α-Syn toxicity in mice and yeast by increasing the higher-order species of α-Syn. Herein, we investigated whether deletion of the TG2 encoding gene could mitigate the toxicity of α-Syn in vivo . Compared with α-Syn transgenic (Syn Tg ) mice, TG2 null /α-Syn transgenic mice (TG2 KO /Syn Tg ) exhibited a reduced amount of phosphorylated α-Syn aggregates and fewer proteinase K-resistant α-Syn aggregates in sections of brain tissue. Neuritic processes that are depleted in Syn Tg mice compared to wild-type mice were preserved in double TG2 KO /Syn Tg mice. Additionally, the neuroinflammatory reaction to α-Syn was attenuated in TG2 KO /Syn Tg animals. These neuropathological markers of diminished α-Syn toxicity in the absence of TG2 were associated with better motor performance on the rotarod and balance beam. These results suggest that deleting TG2 reduces the toxicity of α-Syn in vivo and improves the behavioral performance of Syn Tg mice. Accordingly, these findings collectively support pharmacological inhibition of TG2 as a potential disease modifying therapeutic strategy for α-synucleinopathies.